2017
DOI: 10.3390/ijms19010004
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Potential of Monoterpenes: A Case of Small Molecules Punching above Their Weight

Abstract: Monoterpenes belong to the terpenoids class of natural products and are bio-synthesized through the mevalonic acid pathway. Their small molecular weight coupled with high non-polar nature make them the most abundant components of essential oils which are often considered to have some general antioxidant and antimicrobial effects at fairly high concentrations. These compounds are however reported to have antidiabetic effects in recent years. Thanks to the ingenious biosynthetic machinery of nature, they also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 138 publications
(214 reference statements)
1
37
0
1
Order By: Relevance
“…In vitro and in vivo studies have revealed the effects of monoterpenes in diabetes, insulin resistance and obesity (8). In vitro studies on various cell lines (including pancreatic β cells, muscle, adipocyte and hepatic cells) revealed that besides carvacrol and thymol that have a phenolic skeleton, most monoterpenes do not have the properties of direct radical scavengers due to their antidiabetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have revealed the effects of monoterpenes in diabetes, insulin resistance and obesity (8). In vitro studies on various cell lines (including pancreatic β cells, muscle, adipocyte and hepatic cells) revealed that besides carvacrol and thymol that have a phenolic skeleton, most monoterpenes do not have the properties of direct radical scavengers due to their antidiabetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Lavender essential oils largely comprised of camphor and fenchone (45.25% total composition), were also found to possess antioxidant properties in an alloxan induced rat model of diabetes ( Sebai et al, 2013 ), again raising the possibility that these compounds possess hepatoprotective properties. There have also been recent claims that monoterpenes may have anti-diabetic properties ( Habtemariam, 2017 ) and may modulate cholesterol synthesis via the inhibition of HMG-CoA reductase ( Clegg et al, 1982 ; Elson and Yu, 1994 ; Ren and Gould, 1994 ). Finally, it has been shown that several of these monoterpenes can be synthesized and released by fungi ( Elke et al, 1999 ), raising the possibility that commensal fungi could be impacting liver function via Olfr57.…”
Section: Discussionmentioning
confidence: 99%
“…Using MTs, we were able to detect a novel regulatory domain in the carboxyl-terminal domain of the K2P2.1 channel. Moreover, the growing number of studies on the use of MTs for the treatment of neuropathy (Abuhamdah et al, 2015;Porres-Martinez et al, 2016), as well as for treating diabetes (Habtemariam, 2017), points to the need for better understanding of the effect of MTs on cell components, such as K2P channels, which are involved in these conditions.…”
Section: Discussionmentioning
confidence: 99%